Neoadjuvant chemotherapy and extrapleural pneumonectomy of malignant pleural mesothelioma with or without hemithoracic radiotherapy (SAKK 17/04): a randomised, international, multicentre phase 2 trial. Issue 16 (December 2015) - Stahel, Rolf A; Riesterer, Oliver; Xyrafas, Alexandros; Opitz, Isabelle; Beyeler, Michael; Ochsenbein, Adrian; Früh, Martin; Cathomas, Richard; Nackaerts, Kristiaan; Peters, Solange; Mamot, Christoph; Zippelius, Alfred; et al.
Summary: Background: Postoperative hemithoracic radiotherapy has been used to treat malignant pleural mesothelioma, but it has not been assessed in a randomised trial. We assessed high-dose hemithoracic radiotherapy after neoadjuvant chemotherapy and extrapleural pneumonectomy in patients with malignant pleural mesothelioma. Methods: We did this phase 2 trial in two parts at 14 hospitals in Switzerland, Belgium, and Germany. We enrolled patients with pathologically confirmed malignant pleural mesothelioma; resectable TNM stages T1–3 N0–2, M0; WHO performance status 0–1; age 18–70 years. In part 1, patients were given three cycles of neoadjuvant chemotherapy (cisplatin 75 mg/m 2 and pemetrexed 500 mg/m 2 on day 1 given every 3 weeks) and extrapleural pneumonectomy; the primary endpoint was complete macroscopic resection (R0–1). In part 2, participants with complete macroscopic resection were randomly assigned (1:1) to receive high-dose radiotherapy or not. The target volume for radiotherapy encompassed the entire hemithorax, the thoracotomy channel, and mediastinal nodal stations if affected by the disease or violated surgically. A boost was given to areas at high risk for locoregional relapse. The allocation was stratified by centre, histology (sarcomatoid vs epithelioid or mixed), mediastinal lymph node involvement (N0–1 vs N2), and T stage (T1–2 vs T3). The primary endpoint of part 1 was the proportion of patients achieving complete macroscopic resection (R0 and R1). The primary endpoint in part 2 was locoregional relapse-free survival, analysed by intention to treat. The trial is registered withClinicalTrials.gov, numberNCT00334594 . Findings: We enrolled patients between Dec 7, 2005, and Oct 17, 2012. Overall, we analysed 151 patients receiving neoadjuvant chemotherapy, of whom 113 (75%) had extrapleural pneumonectomy. Median follow-up was 54·2 months (IQR 32–66). 52 (34%) of 151 patients achieved an objective response. The most common grade 3 or 4 toxic effects were neutropenia (21 [14%] of 151 patients), anaemia (11 [7%]), and nausea or vomiting (eight [5%]). 113 patients had extrapleural pneumonectomy, with complete macroscopic resection achieved in 96 (64%) of 151 patients. We enrolled 54 patients in part 2; 27 in each group. The main reasons for exclusion were patient refusal (n=20) and ineligibility (n=10). 25 of 27 patients completed radiotherapy. Median total radiotherapy dose was 55·9 Gy (IQR 46·8–56·0). Median locoregional relapse-free survival from surgery, was 7·6 months (95% CI 4·5–10·7) in the no radiotherapy group and 9·4 months (6·5–11·9) in the radiotherapy group. The most common grade 3 or higher toxic effects related to radiotherapy were nausea or vomiting (three [11%] of 27 patients), oesophagitis (two [7%]), and pneumonitis (two [7%]). One patient died of pneumonitis. We recorded no toxic effects data for the control group. Interpretation: Our findings do not support the routine use of hemithoracic radiotherapy for malignant pleural mesothelioma after neoadjuvant chemotherapy and extrapleural pneumonectomy. Funding: Swiss Group for Clinical Cancer Research, Swiss State Secretariat for Education, Research and Innovation, Eli Lilly.